(NaBETKA(B. (NlOG)QÆKA(B. (NmATEMATIKA(B. :s)E (NMETODI^NIJ POS)QÆBNIK (B/s)E - (NqKIMENKO(B, (NsW)QÆTLANA æWANÆWNA(B,s)E; (NbUDNIJ (B, (Nb(B. )Qã. ,s)E; (NbURLA^UK (B, (Nl(B. (Nf(B.s (ND(B-(NR PSIHOLOG(B. (NNAUK(B, (NPROF(B. ,s; (NpLAHOTN)QÆK (B, (No(B. (Nw(B. ,s)E ((NtERNOP)QÆLX (B:s)E (NnAW^ALXNA KNIGA (B- (NbOGDAN(B,s, 2001)
(Nu POS)QÆBNIKU PODANO DOBÆRKI WÆR[ÆW(B, (NZAGADKI(B, (NSKOROMOWKI(B, (NPOTÆ[KI(B, (NKAZKI(B, (NCÆKAWÆ LOGÆ^NÆ WPRAWI Æ REBUSI(B, (N]O DOPOMOVUTX URÆZNOMANÆTNITI NAW^ALXNÆ ZANQTTQ Z MOLOD[IMI [KOLQRAMI(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NdO[K)QÆLXNA OSWÆTAs)E -- (NmATEMATIKAs; (NDO[K)QÆLXNA PEDAGOGÆKAs)E; (NLOG)QÆKAs)E; (NZAGADKIs